Causes And Consequences Of Changes In Algal Community Structure Of Arctic Tundra Ponds From Barrow, Alaska - Vargas Medrano, Mariana (ScholarWorks@UTEP, 2011)
Algal communities in the Arctic are highly sensitive to environmental change, such as longer growing seasons and changes in ice cover. On the north slope of Alaska, ponds and lakes cover large portions of the total land area. We surveyed the periphytic algal communities in tundra ponds from Barrow, Alaska to assess environmental effects on their populations. Samples were collected in August 2008-10 from two main study areas: the IBP (the International Biological Program), which was also studied in 1970-71 but now is located near to human settlements, and the BEO (Barrow Environmental Observatory), which is within a protected area. The algal community composition in the IBP ponds has changed dramatically over the past 40 years, with many new taxa observed in the recent samples. However, gross taxonomic composition in IBP Pond B was somewhat similar between 2010 and 1972. The dominant algal groups in 2008-10 were Cyanophyta and Bacillariophyceae. Cyanophyta tended to dominate under low nutrient, high light conditions in the spring and early summer, whereas, Bacillariophyceae dominated when nutrient levels were highest in late summer. Moreover, these two algal groups fluctuated in relative abundance twice during the growing season. We also found some algal taxa at some sites that were bioindicators of nutrient-rich conditions, but they were rather low in relative abundance; however, we recommend paying attention to these species because they may be important pollution indicators in the future. It is important to understand algal processes in aquatic ecosystems in the Arctic, since any change in the primary producers can cause a cascading effect on the whole ecosystem and have impacts for global carbon balances.